2017
DOI: 10.1016/j.scitotenv.2017.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure of firefighters to polycyclic aromatic hydrocarbons in non-fire work environments

Abstract: This work aims to characterize personal exposure of firefighters to polycyclic aromatic hydrocarbons (PAHs) in non-fire work environments (fire stations), and assesses the respective risks. Eighteen PAHs (16 considered by USEPA as priority pollutants, dibenzo[a,l]pyrene and benzo[j]fluoranthene) were monitored in breathing zones of workers at five Portuguese fire stations during a normal shift. The obtained levels of PAHs fulfilled all existent occupational exposure limits as well as air quality guidelines wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 105 publications
(147 reference statements)
0
16
0
1
Order By: Relevance
“…Climate changes and global warming have substantially contributed to increase forest fire episodes, with longer fire season and more potent fires (de Rigo et al, 2017;San-Miguel-Ayanz et al, 2018). Forest fire emissions release large amounts of several hazardous gaseous and particulate pollutants: particulate matter, carbon monoxide, nitrogen dioxide, and volatile organic compounds (including polycyclic aromatic hydrocarbons (PAHs), acetaldehyde, formaldehyde, benzene, toluene, phenol, xylene, acrolein, and ethylbenzene) (Abrard et al, 2019;Adame et al, 2018;de la Barrera et al, 2018;McClure and Jaffe, 2018;Wentworth et al, 2018;Oliveira et al, 2015Oliveira et al, , 2017aOliveira et al, 2017b;Fent et al, 2013Fent et al, , 2014Fent et al, 2017Fent et al, , 2015Park et al, 2015;Keir et al, 2017;Hsu et al, 2011;Pleil et al, 2014). Some of these compounds are classified by the International Agency for Research on Cancer (IARC) as potential/possible carcinogens to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Climate changes and global warming have substantially contributed to increase forest fire episodes, with longer fire season and more potent fires (de Rigo et al, 2017;San-Miguel-Ayanz et al, 2018). Forest fire emissions release large amounts of several hazardous gaseous and particulate pollutants: particulate matter, carbon monoxide, nitrogen dioxide, and volatile organic compounds (including polycyclic aromatic hydrocarbons (PAHs), acetaldehyde, formaldehyde, benzene, toluene, phenol, xylene, acrolein, and ethylbenzene) (Abrard et al, 2019;Adame et al, 2018;de la Barrera et al, 2018;McClure and Jaffe, 2018;Wentworth et al, 2018;Oliveira et al, 2015Oliveira et al, , 2017aOliveira et al, 2017b;Fent et al, 2013Fent et al, , 2014Fent et al, 2017Fent et al, , 2015Park et al, 2015;Keir et al, 2017;Hsu et al, 2011;Pleil et al, 2014). Some of these compounds are classified by the International Agency for Research on Cancer (IARC) as potential/possible carcinogens to humans.…”
Section: Introductionmentioning
confidence: 99%
“…One, by Baxter et al (2014), measured PM 2.5 in fire stations in Cincinnati, Ohio over an 8-hour period on a single day and found values higher than what was observed in this study (average PM 2.5 in truck bay was 55μg/m 3 compared to our values of 14-42μg/m 3 ). [22] Two other recent studies by Oliveira et al [23, 24] examined levels of particle-bound PAHs in breathing zones in firefighters at fire stations in Portugal. They indicated that the likely source of PAHs was the vehicular emissions in the fire stations, although they noted observed levels of PAHs fell below many relevant occupational exposure limits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these recent studies collected data from sampling periods of either 4 or 8 hours, much less than the 24-hour shifts experienced by Massachusetts firefighters, which limits the generalizability of these previous studies to our study population. In addition, neither Baxter et al [22], nor the two studies by Oliveria et al [23, 24] include data on contaminant levels outside, which can serve as an important comparison to understand general background levels. There is a lack of information in the scientific literature and limited information available on firefighter exposure to PM 2.5 and PAHs in the fire station, which highlights the need for further research on this topic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Michelle 등은, 봄, 여름, 가을 3개 계절에 걸쳐 아틀란타 도 심지역 소방청사 내 PM 10 , PM 2.5 농도를 모니터링 한 결과, 가을에 PM 10 이 유의하게 높았음을 확인하였고 (7) , Diane Ivy 등은 소방장비를 작동할 때 디젤배출물로부터 PM 10 이 배 출되는것이 확인되었는데 (8) , 본 연구에서 측정된 미세먼지 (12) . Oliveria의 연구에서는 소방서에 서 소방관들의 다환방향족탄화수소의 개인적 노출특성과 위험도 평가를 실시한 결과 연료, 차량배기가스, 윤활유 사 용 등이 PAH노출의 주요 원인으로 확인되었다.…”
Section: 서 론unclassified